The Impact of Professional Capital and its Role in Organizational Innovation at Private Banks Operating in Baghdad: Dampak Modal Profesional dan Perannya dalam Inovasi Organisasi di Bank Swasta yang Beroperasi di Baghdad - Mohammed, Dheyaa Talib (Academia Open, 2026)
General Background: Human capital and intellectual capital are widely recognized as key resources in organizational development and knowledge-based economies. Specific Background: Organizations increasingly rely on knowledge creation, social capital, and learning processes to support innovation activities. Knowledge Gap: Despite extensive theoretical development, there is limited integration of different capital perspectives in explaining organizational innovation. Aims: This study examines the role of human capital, social capital, and organizational learning in shaping innovation processes. Results: The findings indicate that knowledge creation, employee competencies, and organizational learning mechanisms contribute to innovation development within firms. Novelty: The study integrates multiple theoretical perspectives, including knowledge-based theory and social capital theory, to provide a comprehensive understanding of innovation processes. Implications: The results highlight the importance of aligning human resource practices and knowledge management strategies to support sustainable innovation in organizations. Keywords: Human Capital, Organizational Innovation, Knowledge Management, Social Capital, Organizational Learning Key Findings Highlights Employee competencies support knowledge creation processes Learning mechanisms facilitate innovation development Social relationships strengthen collaborative knowledge exchange